Enhancing the aqueous solubility and dissolution of olanzapine using freeze-drying - Mudit Dixit; Ashwini Gopalkrishna Kini; Parthasarthi Keshavarao Kulkarni (Universidade de São Paulo, 2011)
The aim of the present study was to develop an olanzapine freeze-dried tablet (FDT). The solubility and dissolution rate of poorly water-soluble olanzapine was improved by preparing a freeze-dried tablet of olanzapine using the freeze-drying technique . The FDT was prepared by dispersing the drug in an aqueous solution of highly water-soluble carrier materials consisting of gelatin, glycine, and sorbitol. The mixture was poured in to the pockets of blister packs and then was subjected to freezing and lyophilisation. The FDT was characterised by DSC, XRD and SEM and was evaluated for saturation solubility and dissolution. The samples were stored in a stability chamber to investigate their physical stability. Results obtained by DSC and X-ray were analysed and showed the crystalline state of olanzapine in FDT transformation to the amorphous state during the formation of FDT. Scanning electron microscope (SEM) results suggest reduction in olanzapine particle size. The solubility of olanzapine from the FDT was observed to be nearly four and a half times greater than the pure drug. Results obtained from dissolution studies showed that olanzapine FDT significantly improved the dissolution rate of the drug compared with the physical mixture (PM) and the pure drug. More than 90% of olanzapine in FDT dissolved within 5 minutes, compared to only 19.78% of olanzapine pure drug dissolved over the course of 60 minutes. In a stability test, the release profile of the FDT was unchanged, as compared to the freshly prepared FDT after 90 days of storing. O objetivo do presente estudo foi desenvolver comprimidos liofilizados de olanzapina (FDT). A solubilidade e a taxa de dissolução da olanzapina, fracamente solúvel em água, foram melhoradas com a preparação de comprimidos liofilizados de olanzapina usando a técnica de liofilização. O FDT foi preparado por dispersão do fármaco em solução aquosa de materiais altamente solúveis em água, como gelatina, glicina e sorbitol. A mistura foi colocada em blisters e, então, submetida ao congelamento e liofilização. O FDT foi caracterizado por DSC, Difração de Raios X e microscopia eletrônica de varredura(SEM) e avaliaram-se a solubilidade de saturação e a dissolução. As amostras for5am armazenadas em câmara de estabilidade para investigar a estabilidade física. Os resultados obtidos com DSC e Raios X foram analisados e mostraram a transformação do estado cristalino da olanzepina em FDT no estado amorfo durante a formação do FDT. Os resultados da SEM sugerem a redução do tamanho das partículas de olanzapina. A solubilidade da olanzapina do FDT melhorou significativamente a taxa de dissolução do fármaco comparativamente à mistura física (PM) e ao fármaco puro. Mais do que 90% da olanzepina no FDT dissolveu em 5 minutos, comparativamente aos 19,78% do fármaco puro dissolvido em 60 minutos. No teste de estabilidade, o perfil de liberação da FDT mostrou-se inalterado, quando comparado com o FDT recém-preparado, após 90 dias de armazenamento.